Evaluation of drug release from topical dosage forms and permeability prediction through the skin barrier (review) - N. B. Melnikova; I. A. Sheferov; A. A. Emasheva; A. A. Sheferova; D. A. Panteleev; A. I. Slivkin (Разработка и регистрация лекарственных средств)
Introduction. The review considered the basic concepts of drug release and kinetic modeling of this process from dosage forms (DF) according to the dissolution profile using a vertical Franz diffusion cell.Text. Drug release from dosage forms (ointments, gels, transdermal patches and polymer films) is usually described as the processes of drug dissolution in the biological system. Formally, this process, in accordance with pharmacopoeial methods, is assessed using various solubility tests. The theoretical aspects of drug release are based on the theory of mass transfer of substances from a polymer matrix into a system that simulates a biological environment. Drug release can be carried out via the passive diffusion mechanism according to Fick and "non-Fick" diffusion, drug desorption from the inner side of the membrane, as well as other mechanisms. Drug release is determined both lipophilicity and the membrane nature, both various physicochemical parameters of the drug. One of the correlation characteristics of mass transfer is the assessment of the permeability coefficient for a specific membrane that simulates skin. Permeability coefficient describes the rate of penetration of a drug per unit concentration in distance/time units. An example of relationship of "structure-permeability" correlation are the equations relating the permeability constant and lipophilicity to the molecular weight of the drug. The paper showed statistical methods of data analysis (MANOVA, ANOVA) and model-dependent methods (zero order, first order, Higuchi model, Korsmeyer – Peppas model, Hixson – Crowell model, etc.). The ideal drug delivery of non-degradable and non-disaggregating drugs describes as drug release model by zero-order reaction. For drug release of water-soluble drugs from a porous matrix, first-order reaction model is more typical. Kinetic models of fractional power functions are used usually as the cube root law (Hixson – Crowell model) or the square root law (Higuchi model) to describe the process of drug release from gels and dermal films and patches. The Korsmeyer – Peppas model allows us to evaluate the mechanism of mass transfer with Fickian diffusion or another process.Conclusion. Mathematical modeling of the drug release kinetics from soft dosage forms is an important element for the development and optimization of their compositions. The study of the drugs release from soft dosage forms, including TTS and polymer films, as well as the release from solid dosage forms, is based on establishing correlations between the kinetics of the release and dissolution profile. The main release models, regardless of the DF, remain the following models: zero order, first order, Korsmeyer – Peppas, Higuchi, Hickson – Crowell, the empirical or semi-empirical constants of which vary significantly depending on the DF and the release mechanism (Fickian diffusion or another drug mass transfer mechanism). Correlation relationships QSPeR or QSPR, using the coefficients of permeability, diffusion and lipophilicity, provide information on the mass transfer of drugs through the skin.